Cobalt plating additive for filling cobalt in integrated circuits, cobalt electroplating solution and electroplating method
By using benzotetrazolium compounds and sulfur-containing organic matter as cobalt plating additives in integrated circuits, the cobalt ion deposition and hydrogen precipitation are synergistically inhibited, and high-quality cobalt interconnection lines without voids are achieved, and Cu interconnection lines are solved The problems of increased line resistivity and Cu penetration improve the performance of integrated circuits.
Patent Information
- Application Number
- CN202211559801.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-06
AI Technical Summary
In integrated circuits, as the chip process size decreases, the line resistivity of Cu interconnect lines increases exponentially, resulting in an increase in RC delay, affecting the conductivity and transmission speed. At the same time, Cu atoms are prone to permeate the Si substrate, reducing semiconductor performance.
A new type of cobalt plating additive, including benzotetrazolium compounds as inhibitors and sulfur-containing organic compounds as wetting agents, is used to inhibit cobalt ion deposition during the electroplating process, and reduce the negative impact of hydrogen precipitation. Achieve high-quality cobalt interconnects without voids in micropores.
It realizes cobalt interconnection lines with thin cobalt surface and no void defects, and has good uniformity of plating, with good defect-free hole filling capability, reduces line resistance and RC delay, and improves the conductivity and transmission of integrated circuits. speed.
Smart Images

Figure CN115874236B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electroplating, and in particular relates to a cobalt plating additive suitable for filling cobalt in integrated circuit circuits, a cobalt electroplating solution and an electroplating method. Background Art
[0002] The International Technology Roadmap for Semiconductors pointed out in 2004 that according to the development of Moore's Law, when integrated circuits reach the nm level, the line resistance of Cu as an interconnect material no longer meets the chip requirements. However, it was not until the chip process was reduced to below 28nm that materials that can replace Cu as interconnects attracted great attention. At present, the density of integrated circuits is gradually increasing, and the internal MOS electrode structure is gradually miniaturized, making the size of the interconnect line smaller than the mean free path of copper electrons, especially in chips with a 7nm process. Therefore, continuing to use copper as an interconnect material on this basis will cause the line resistance to gradually increase and affect chip efficiency. This is because when the mean free path of Cu electrons is lower than the line width of the interconnect line, electrons are severely scattered at the grain boundaries and interfaces, causing the resistivity of the copper line to increase exponentially, and the increasing resistance leads to an increase in RC delay, which reduces the conductivity of the integrated circuit, increases power consumption, and affects the transmission speed. In addition, due to the electromigration phenomenon, the interconnect Cu material is prone to penetration in the chip Si substrate, that is, Cu atoms diffuse into the Si wafer, resulting in a decrease in the performance of the substrate semiconductor. Therefore, an isolation layer / barrier layer must be sputtered to isolate the contact between the metal Cu and the chip Si to reduce the penetration of Cu ions. The available barrier layer currently mainly adopts the PVD method to sputter TiN or TaN as the barrier layer.
[0003] The next step is to use metal Co as a wetting layer, which can not only wet the Cu interconnects during deposition, but also hinder the diffusion of Cu atoms. However, when the chip process size gradually decreases to the single nm level, the thickness of the barrier layer will also greatly affect the performance of the interconnects, mainly because the thickness of the barrier layer is almost impossible to adjust. Then using metal Co as an interconnect material instead of a wetting layer can not only reduce or eliminate the barrier layer, but also reduce the resistance increase caused by grain boundary scattering. In order not to affect the subsequent Damascus copper plating process, it will be a meaningful research direction to use electroplated Co technology to fill the trenches / blind holes in the chip.
[0004] Metal Co has a large cathode polarization overpotential during the electrodeposition process, and therefore, even in the absence of additives, the prepared coating also has a certain leveling and filling capacity. In addition, the deposition potential of Co ions is significantly negative to the potential of hydrogen precipitation, which requires the negative impact of hydrogen precipitation to be considered during the electrodeposition process, i.e., reducing the Co deposition efficiency and easily forming pinholes in the coating. Taking the above factors into consideration, the selection of additives in the plating solution should meet the following points: first, the selection of inhibitors, which can be well adsorbed on the cathode surface to hinder the Co ion deposition process, and should also have no bonded interaction with the substrate to avoid doping during the deposition process. The second is the selection of surfactants, which can well discharge the hydrogen bubbles precipitated on the surface of the cathode, and hinder the surface force with hydrogen during the Co grain deposition nucleation process, reducing the pinholes caused by hydrogen precipitation. Therefore, the additive system selected in the present invention has a greater research significance for metal cobalt as an interconnect material in the method of electrochemical deposition. Summary of the invention
[0005] The first object of the present invention is to provide a novel additive having an effective inhibitory effect and capable of filling micropores with cobalt. The novel additive can be used to achieve void-free cobalt filling in micropores.
[0006] A second object of the present invention is to provide a cobalt electroplating solution and an electroplating method.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A cobalt plating additive for cobalt filling of integrated circuits, comprising an inhibitor, wherein the inhibitor is a combination of one or more benzotetrazolyl compounds, and the structural formula of the benzotetrazolyl compound is shown in Formula I:
[0009]
[0010] In the formula, R is an alkyl chain, a phenyl group, a phenyl group containing other substituent functional groups, or a nitro group; R1, R2, R3, and R4 are the same or different and are one of hydrogen, a nitro group, and an alkyl group; R5 and R6 are the same or different and are one of hydrogen, a halogen group, an ester group, a carbonyl group, and an alkyl group.
[0011] Furthermore, the cobalt plating additive also includes a wetting agent, and the wetting agent is a sulfur-containing organic matter.
[0012] The beneficial effects of the present invention compared to the prior art are as follows:
[0013] The mechanism of action of each component of the present invention is: Figure 1The polarization curves of the base plating solution without any additives, the base plating solution containing a benzotetrazolyl compound inhibitor, the base plating solution containing a wetting agent, and the base plating solution containing both a benzotetrazolyl compound inhibitor and a wetting agent are shown in Figure 2. The addition of the benzotetrazolyl compound inhibitor greatly increases the cathode polarization, indicating that the benzotetrazolyl compound inhibitor has a strong inhibitory effect on the deposition of cobalt. The addition of the wetting agent reduces the polarization of cobalt deposition to a certain extent and has a certain promoting effect. Under the condition of the presence of the benzotetrazolyl compound inhibitor, the addition of the wetting agent has almost no effect. It shows that the promoting effect of the wetting agent will be shielded by the benzotetrazolyl compound inhibitor. Therefore, during the electroplating process, although the mass transfer of the wetting agent is higher than that of the benzotetrazolyl compound inhibitor on the surface and the opening, due to the convection condition, sufficient benzotetrazolyl compound inhibitor can be transported near the cathode, so that the cobalt growth on the plane and the opening is inhibited. In the micropores, the mass transfer of the benzotetrazolyl compound inhibitor is limited, while the wetting agent can enter relatively freely, making the growth in the micropores faster. Therefore, under the synergistic effect of the benzotetrazolyl compound inhibitor and the wetting agent, the electroplating system exhibits extremely excellent selectivity. The surface cobalt thickness is very small and the filling rate is very high.
[0014] The addition of the novel inhibitor of the present invention can obtain cobalt interconnects with thinner surface cobalt and no void defects, and the plating uniformity is good. Compared with the prior art, the present invention has good defect-free hole filling ability and lower surface cobalt thickness. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Linear polarization curves of the basic plating solution containing different additives;
[0016] Figure 2 The surface roughness test diagrams of Example 1, Example 2 and Example 3 are shown;
[0017] Figure 3 This is a slice diagram of Example 1 of the present invention;
[0018] Figure 4 This is a slice diagram of Example 2 of the present invention;
[0019] Figure 5 This is a slice diagram of Example 3 of the present invention;
[0020] Figure 6 This is a slice diagram of Example 4 of the present invention;
[0021] Figure 7 This is a slice diagram of Example 5 of the present invention;
[0022] Figure 8 This is a slice diagram of Example 6 of the present invention;
[0023] Fig. 9 This is a slice diagram of Example 7 of the present invention;
[0024] Fig.10 This is a slice diagram of Example 8 of the present invention;
[0025] Fig.11 This is a slice diagram of Example 9 of the present invention. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Specific implementation method 1
[0028] A cobalt plating additive for cobalt filling of integrated circuits includes an inhibitor, wherein the inhibitor contains a functional group that inhibits the reduction of cobalt ions. The inhibitor is a combination of one or more benzotetrazolyl compounds, and the structural formula of the benzotetrazolyl compound is shown in Formula I:
[0029]
[0030] In the formula, R is an alkyl chain, a phenyl group, a phenyl group containing other substituent functional groups, or a nitro group; R1, R2, R3, and R4 are the same or different and are one of hydrogen, a nitro group, and an alkyl group; R5 and R6 are the same or different and are one of hydrogen, a halogen group, a nitro group, an ester group, a carbonyl group, and an alkyl group.
[0031] Preferably, R1 and R2 are both hydrogen, R3 and R4 are one of hydrogen, nitro and alkyl, and R5 and R6 are preferably one of hydrogen, nitro, alkyl and carbonyl.
[0032] Furthermore, the cobalt plating additive also includes a wetting agent, which is a sulfur-containing organic matter. The wetting agent is conducive to the adsorption of the inhibitor, and the synergistic effect of the inhibitor and the wetting agent effectively improves the dispersibility and pore filling ability of the plating solution, thereby realizing high-quality cobalt interconnects without voids.
[0033] Further, the benzotetrazolyl compounds include but are not limited to: 3-(4-nitrophenyl)-5-methyl-2-phenyl tetrazolium chloride, tetranitro tetrazolium blue, iodonitrotetrazolium violet, tetrazolium blue, 2,3-bis(4-nitrophenyl)-5-phenyl tetrazolium chloride hydrate, 2,3,5-triphenyl tetrazolium chloride, 2,3-diphenyl-5-carboxy tetrazolium chloride, 2,3-diphenyl-5-methyl tetrazolium chloride, 2,3-diphenyl-5-ethyl tetrazolium chloride, 2,3-bis(4-ethylphenyl)-5-phenyl tetrazolium chloride, 2,3-di(p-tolyl)-5-phenyl tetrazolium chloride, 2,3-diphenyl-5-(4-methoxyphenyl) tetrazolium chloride, 2,3-bis(4-tolyl)-5-(4-cyanophenyl) tetrazolium chloride, nitro tetrazolium blue chloride or thiazolium blue tetrazolium bromide.
[0034] Furthermore, the sulfur-containing organic matter is a combination of one or more of 3-mercaptopropane sulfonic acid sodium salt, dimercaptopropane sulfonate sodium salt, 1,3-dimercaptopropane, sodium dodecyl sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, 1-hexadecane sulfonic acid sodium salt, polydisulfide propane sulfonate sodium salt, and methane disulfonic acid disodium salt. Specific implementation method 2
[0036] A cobalt electroplating solution comprises the cobalt plating additive described in the first specific implementation manner.
[0037] Furthermore, the concentration of the inhibitor in the cobalt electroplating solution is 5 mg / L-500 mg / L, the wetting agent is sulfur-containing organic matter, and the concentration of the wetting agent is 1 mg / L-50 mg / L.
[0038] Preferably, the concentration of the inhibitor in the cobalt electroplating solution is 10 mg / L-50 mg / L, and the concentration of the wetting agent is 10 mg / L-20 mg / L.
[0039] Furthermore, the electroplating cobalt solution also includes cobalt sulfate heptahydrate, boric acid and halogen ions, the concentration of cobalt sulfate heptahydrate is 50-100 g / L, the concentration of halogen ions is 10-100 mg / L, and the concentration of boric acid is 20-50 g / L.
[0040] Furthermore, the halogen ion includes chloride ion, bromide ion or iodide ion. Specific implementation method three
[0042] A method for electroplating using the cobalt electroplating solution described in the second embodiment, wherein a substrate containing micropores is placed in the cobalt electroplating solution, and electroplating is performed in a constant current manner under air stirring, and the current density of the electroplating is 0.5 to 1.5 A·dm -2 During the cobalt plating process, the plating solution temperature is controlled at 10-35°C.
[0043] Embodiment 1:
[0044] Cobalt plating solution composition: cobalt sulfate heptahydrate: 50g / L, boric acid: 20g / L, chloride ion: 20mg / L, inhibitor iodonitrotetrazolium violet: 20mg / L, wetting agent 1-hexadecanesulfonic acid sodium salt: 10mg / L. Current density 0.50A / dm 2 , the electroplating time is 2 hours. The diameter of the micropores in the electroplated substrate is 50 microns.
[0045] Before electroplating, the electroplating substrate needs to be degreased, derusted and surface activated. The specific steps are: degreasing with 80℃ degreasing solution for 5 minutes → room temperature water washing for 5 minutes → acetone degreasing for 5 minutes → room temperature water washing for 5 minutes → 10% concentrated sulfuric acid derusting for 5 minutes → room temperature water washing for 5 minutes → room temperature pre-immersion for 3 minutes → room temperature water washing for 5 minutes.
[0046] Among them, the degreasing liquid composition is 0.25mol·L -1 NaOH, 0.04 mol·L -1 Na2SiO3·9H2O, 0.15mol·L - 1 Na3PO4·12H2O, 0.50mol·L -1 Na2CO3, degreasing temperature is 80℃, and the time is 5 to 10 minutes.
[0047] Figure 2 (a) Iononitrotetrazolyl violet was used as an inhibitor at a concentration of 20 mg / L and a current density of 0.5 A / dm 2 After 2 hours of electroplating, the roughness, root mean square roughness Rq and average roughness Ra of the electroplated substrate surface were 134nm and 111nm, respectively, indicating that the cobalt coating was finely crystallized and smooth. Figure 3 This is a cross-sectional view after electroplating. Perfect cobalt filling is achieved in the 50-micron hole, and the surface cobalt thickness is less than 5 microns with good uniformity, which facilitates the subsequent chemical mechanical polishing process.
[0048] Embodiment 2:
[0049] Cobalt plating solution composition: cobalt sulfate heptahydrate: 80g / L, boric acid: 35g / L, chloride ion: 50mg / L, inhibitor 2,3-diphenyl-5-methyltetrazole chloride: 30mg / L, wetting agent sodium dodecyl sulfate: 50mg / L. Current density 1.0A / dm 2 , the electroplating time is 2 hours. The diameter of the micropores on the electroplated substrate is 100 microns.
[0050] Before electroplating, the electroplating substrate needs to be degreased, derusted and surface activated. The specific steps are: degreasing with 80℃ degreasing solution for 5 minutes → room temperature water washing for 5 minutes → acetone degreasing for 5 minutes → room temperature water washing for 5 minutes → 10% concentrated sulfuric acid derusting for 5 minutes → room temperature water washing for 5 minutes → room temperature pre-immersion for 3 minutes → room temperature water washing for 5 minutes.
[0051] Among them, the degreasing liquid composition is 0.25mol·L -1 NaOH, 0.04 mol·L -1 Na2SiO3·9H2O, 0.15mol·L - 1 Na3PO4·12H2O, 0.50mol·L -1 Na2CO3, degreasing temperature is 80℃, and the time is 5 to 10 minutes.
[0052] Figure 2 (b) 2,3-Diphenyl-5-methyltetrazolyl chloride was used as an inhibitor at a concentration of 30 mg / L and a current density of 1.0 A / dm 2 After 2 hours of electroplating, the roughness, root mean square roughness Rq and average roughness Ra of the electroplated substrate surface were 121nm and 98.8nm respectively, indicating that the cobalt coating was finely crystallized and smooth. Figure 4 This is a cross-sectional view after electroplating. Perfect cobalt filling is achieved in the 100-micron hole, and the surface cobalt thickness is less than 10 microns with good uniformity, which facilitates the subsequent chemical mechanical polishing process.
[0053] Embodiment 3:
[0054] Cobalt plating solution composition: cobalt sulfate heptahydrate: 100g / L, boric acid: 50g / L, chloride ion: 100mg / L, inhibitor 2,3-bis(4-methylphenyl)-5-(4-cyanophenyl) tetrazolium chloride: 10mg / L, wetting agent disodium methane disulfonate: 20mg / L. Current density 1.50A / dm 2 , the electroplating time is 2 hours. The diameter of the micropores in the electroplated substrate is 150 μm.
[0055] Before electroplating, the electroplating substrate needs to be degreased, derusted and surface activated. The specific steps are: degreasing with 80℃ degreasing solution for 5 minutes → room temperature water washing for 5 minutes → acetone degreasing for 5 minutes → room temperature water washing for 5 minutes → 10% concentrated sulfuric acid derusting for 5 minutes → room temperature water washing for 5 minutes → room temperature pre-immersion for 3 minutes → room temperature water washing for 5 minutes.
[0056] Among them, the degreasing liquid composition is 0.25mol·L -1 NaOH, 0.04 mol·L -1 Na2SiO3·9H2O, 0.15mol·L- 1 Na3PO4·12H2O, 0.50mol·L -1 Na2CO3, degreasing temperature is 80℃, and the time is 5 to 10 minutes.
[0057] Figure 2 (c) 2,3-bis(4-methylphenyl)-5-(4-cyanophenyl) tetrazolium chloride was used as an inhibitor at a concentration of 10 mg / L and a current density of 1.5 A / dm 2 After 2 hours of electroplating, the roughness, root mean square roughness Rq and average roughness Ra of the electroplated substrate surface were 157nm and 122nm, respectively, indicating that the cobalt coating was finely crystallized and smooth. Figure 5 This is a cross-sectional view after electroplating. Perfect cobalt filling is achieved in the 150-micron hole, and the surface cobalt thickness is less than 20 microns with good uniformity, which facilitates the subsequent chemical mechanical polishing process.
[0058] Embodiment 4:
[0059] Cobalt plating solution composition: cobalt sulfate heptahydrate: 50g / L, boric acid: 30g / L, chloride ion: 30mg / L, inhibitor 2,3-diphenyl-5-carboxytetrazolyl chloride: 5mg / L, wetting agent sodium dodecyl sulfate: 10mg / L. Current density 0.60A / dm 2 , the electroplating time is 2 hours. The diameter of the micropores in the electroplated substrate is 50 microns.
[0060] Before electroplating, the electroplating substrate needs to be degreased, derusted and surface activated. The specific steps are: degreasing with 80℃ degreasing solution for 5min → room temperature water washing for 5min → acetone degreasing for 5min → room temperature water washing for 5min → 10% concentrated sulfuric acid derusting for 5min → room temperature water washing for 5min → room temperature pre-immersion for 3min → room temperature water washing for 5min. The degreasing solution composition is 0.25mol·L -1 NaOH, 0.04 mol·L -1 Na2SiO3·9H2O, 0.15mol·L -1 Na3PO4·12H2O, 0.50mol·L -1 Na2CO3, degreasing temperature is 80℃, and the time is 5 to 10 minutes.
[0061] Figure 6 This is a cross-sectional view after electroplating. Perfect cobalt filling is achieved in the 50-micron hole, and the surface cobalt thickness is less than 20 microns with good uniformity, which facilitates the subsequent chemical mechanical polishing process.
[0062] Embodiment 5:
[0063] Cobalt plating solution composition: cobalt sulfate heptahydrate: 80g / L, boric acid: 40g / L, chloride ion: 50mg / L, inhibitor thiazolyl blue tetrazolium bromide: 100mg / L, wetting agent sodium dithiopropanesulfonate: 20mg / L. Current density 0.90A / dm 2 , the electroplating time is 2 hours. The diameter of the micropores on the electroplated substrate is 100 microns.
[0064] Before electroplating, the electroplating substrate needs to be degreased, derusted and surface activated. The specific steps are: degreasing with 80℃ degreasing solution for 5min → room temperature water washing for 5min → acetone degreasing for 5min → room temperature water washing for 5min → 10% concentrated sulfuric acid derusting for 5min → room temperature water washing for 5min → room temperature pre-immersion for 3min → room temperature water washing for 5min. The degreasing solution composition is 0.25mol·L -1 NaOH, 0.04 mol·L -1 Na2SiO3·9H2O, 0.15mol·L -1 Na3PO4·12H2O, 0.50mol·L -1 Na2CO3, degreasing temperature is 80℃, and the time is 5 to 10 minutes.
[0065] Figure 7 This is a cross-sectional view after electroplating. Perfect cobalt filling is achieved in the 100-micron hole, and the surface cobalt thickness is less than 10 microns with good uniformity, which facilitates the subsequent chemical mechanical polishing process.
[0066] Embodiment 6:
[0067] Cobalt plating solution composition: cobalt sulfate heptahydrate: 55g / L, boric acid: 20g / L, chloride ion: 10mg / L, inhibitor 2,3-di(p-tolyl)-5-phenyltetrazolyl chloride: 100mg / L, wetting agent sodium polydisulfide dipropane sulfonate: 30mg / L. Current density 0.50A / dm 2 , the electroplating time is 2 hours. The diameter of the micropores in the electroplated substrate is 50 microns.
[0068] Before electroplating, the electroplating substrate needs to be degreased, derusted and surface activated. The specific steps are: degreasing with 80℃ degreasing solution for 5min → room temperature water washing for 5min → acetone degreasing for 5min → room temperature water washing for 5min → 10% concentrated sulfuric acid derusting for 5min → room temperature water washing for 5min → room temperature pre-immersion for 3min → room temperature water washing for 5min. The degreasing solution composition is 0.25mol·L -1 NaOH, 0.04 mol·L -1 Na2SiO3·9H2O, 0.15mol·L -1 Na3PO4·12H2O, 0.50mol·L -1Na2CO3, degreasing temperature is 80℃, and the time is 5 to 10 minutes.
[0069] Figure 8 This is a cross-sectional view after electroplating. Perfect cobalt filling is achieved in the 50-micron hole, and the surface cobalt thickness is less than 12 microns with good uniformity, which facilitates the subsequent chemical mechanical polishing process.
[0070] Embodiment 7:
[0071] Cobalt plating solution composition: cobalt sulfate heptahydrate: 90g / L, boric acid: 45g / L, chloride ion: 90mg / L, inhibitor tetrazolium blue: 500mg / L, wetting agent sodium dodecylbenzene sulfonate: 50mg / L. Current density 1.50A / dm 2 , the electroplating time is 2 hours. The diameter of the micropores in the electroplated substrate is 150 μm.
[0072] Before electroplating, the electroplating substrate needs to be degreased, derusted and surface activated. The specific steps are: degreasing with 80℃ degreasing solution for 5min → room temperature water washing for 5min → acetone degreasing for 5min → room temperature water washing for 5min → 10% concentrated sulfuric acid derusting for 5min → room temperature water washing for 5min → room temperature pre-immersion for 3min → room temperature water washing for 5min. The degreasing solution composition is 0.25mol·L -1 NaOH, 0.04 mol·L -1 Na2SiO3·9H2O, 0.15mol·L -1 Na3PO4·12H2O, 0.50mol·L -1 Na2CO3, degreasing temperature is 80℃, and the time is 5 to 10 minutes.
[0073] Fig. 9 This is a cross-sectional view after electroplating. Perfect cobalt filling is achieved in the 150-micron hole, and the surface cobalt thickness is less than 12 microns with good uniformity, which facilitates the subsequent chemical mechanical polishing process.
[0074] Embodiment 8:
[0075] Cobalt plating solution composition: cobalt sulfate heptahydrate: 50g / L, boric acid: 20g / L, chloride ion: 10mg / L, inhibitor nitro tetrazolium chloride: 50mg / L, wetting agent 3-mercaptopropane sulfonic acid sodium salt: 20mg / L. Current density 0.50A / dm 2 , the electroplating time is 2 hours. The diameter of the micropores in the electroplated substrate is 50 microns.
[0076] Before electroplating, the electroplating substrate needs to be degreased, derusted and surface activated. The specific steps are: degreasing with 80℃ degreasing solution for 5min → room temperature water washing for 5min → acetone degreasing for 5min → room temperature water washing for 5min → 10% concentrated sulfuric acid derusting for 5min → room temperature water washing for 5min → room temperature pre-immersion for 3min → room temperature water washing for 5min. The degreasing solution composition is 0.25mol·L -1 NaOH, 0.04 mol·L -1 Na2SiO3·9H2O, 0.15mol·L -1 Na3PO4·12H2O, 0.50mol·L -1 Na2CO3, degreasing temperature is 80℃, and the time is 5 to 10 minutes.
[0077] Fig.10 This is a cross-sectional view after electroplating. Perfect cobalt filling is achieved in the 50-micron hole, and the surface cobalt thickness is less than 15 microns with good uniformity, which facilitates the subsequent chemical mechanical polishing process.
[0078] Embodiment 9:
[0079] Cobalt plating solution composition: cobalt sulfate heptahydrate: 100g / L, boric acid: 50g / L, chloride ion: 100mg / L, inhibitor 2,3-bis(4-methylphenyl)-5-(4-cyanophenyl) tetrazolium chloride: 500mg / L, wetting agent 3-mercaptopropane sulfonic acid sodium salt: 30mg / L. Current density 0.95A / dm 2 , the electroplating time is 2 hours. The diameter of the micropores in the electroplated substrate is 150 μm.
[0080] Before electroplating, the electroplating substrate needs to be degreased, derusted and surface activated. The specific steps are: degreasing with 80℃ degreasing solution for 5min → room temperature water washing for 5min → acetone degreasing for 5min → room temperature water washing for 5min → 10% concentrated sulfuric acid derusting for 5min → room temperature water washing for 5min → room temperature pre-immersion for 3min → room temperature water washing for 5min. The degreasing solution composition is 0.25mol·L -1 NaOH, 0.04 mol·L -1 Na2SiO3·9H2O, 0.15mol·L -1 Na3PO4·12H2O, 0.50mol·L -1 Na2CO3, degreasing temperature is 80℃, and the time is 5 to 10 minutes.
[0081] Fig.11 This is a cross-sectional view after electroplating. Perfect cobalt filling is achieved in the 150-micron hole, and the surface cobalt thickness is less than 15 microns with good uniformity, which facilitates the subsequent chemical mechanical polishing process.
[0082] Table 1
[0083]
[0084]
Claims
1. A cobalt electroplating solution for filling cobalt in integrated circuits, characterized in that: The invention comprises an inhibitor, wherein the inhibitor is a combination of one or more benzotetrazolyl compounds, and the benzotetrazolyl compounds include: 3-(4-nitrophenyl)-5-methyl-2-phenyltetrazolyl chloride, tetranitrotetrazolyl blue, iodonitrotetrazolium violet, tetrazolyl blue, 2,3-bis(4-nitrophenyl)-5-phenyltetrazolyl chloride hydrate, 2,3,5-triphenyltetrazolyl chloride, 2,3-diphenyl-5-carboxytetrazolyl chloride, 2,3-diphenyl-5-methyltetrazolyl chloride, 2,3-diphenyl-5-ethyltetrazolyl chloride, 2,3-bis(4-ethylphenyl)-5-phenyltetrazolyl chloride, 2,3-di(p-tolyl) -5-phenyl tetrazolium chloride, 2,3-diphenyl-5-(4-methoxyphenyl) tetrazolium chloride, 2,3-bis(4-methylphenyl)-5-(4-cyanophenyl) tetrazolium chloride, nitro tetrazolium blue chloride or thiazolium blue tetrazolium bromide; the electroplating cobalt bath also includes a wetting agent, the wetting agent is a sulfur-containing organic matter, the sulfur-containing organic matter is a combination of one or more of 3-mercaptopropane sulfonic acid sodium salt, dimercaptopropane sulfonic acid sodium salt, 1,3-dimercaptopropane, sodium dodecyl sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, 1-hexadecane sulfonic acid sodium salt, polydisulfide dipropane sulfonate sodium, and methane disulfonic acid disodium salt; the concentration of the inhibitor in the electroplating cobalt bath is 5 mg / L-500 mg / L, and the concentration of the wetting agent is 1 mg / L-50 mg / L.
2. The cobalt electroplating solution according to claim 1, characterized in that: The concentration of the inhibitor in the cobalt electroplating solution is 10 mg / L-50 mg / L, and the concentration of the wetting agent is 10 mg / L-20 mg / L.
3. The cobalt electroplating solution according to claim 1, characterized in that: The electroplating cobalt plating solution also includes cobalt sulfate heptahydrate, boric acid and halogen ions. The concentration of the cobalt sulfate heptahydrate is 50-100 g / L, the concentration of the halogen ions is 10-100 mg / L, and the concentration of the boric acid is 20-50 g / L.
4. The cobalt electroplating solution according to claim 3, characterized in that: The halogen ion includes a chloride ion, a bromide ion or an iodide ion.
5. A method for electroplating using the cobalt electroplating solution according to any one of claims 1 to 4, characterized in that: The substrate containing micropores is placed in the cobalt electroplating solution and electroplated using a constant current method under air stirring. The electroplating current density is 0.5~1.5 A·dm -2 During the cobalt plating process, the plating solution temperature is controlled at 10~35℃.
Citation Information
Patent Citations
Copper electroplating solution for filling through hole of IC (Integrated Circuit) carrier plate and electroplating method
CN111424296A